Scattering of seismic waves generated by an irregular seabed - Santos, Paulo (2004)
The changes in the seismic response due to the presence of an irregular elastic seabed, and/or the presence of a water-filled inclusion located under the elastic seabed surface, in the presence of a dilatational spatially harmonic line source, is assessed. The seabed surface deformations and the water-filled inclusions are bi-dimensional.